Evaluation of Peroxidase in Herbal Medicines Based on an Electrochemical Sensor - Yue, Yinzi; Su, Lianlin; Hao, Min; Li, Wenting; Zeng, Li; Yan, Shuai (Frontiers in Chemistry, 2021)
Peroxidases are species-specific. Differences in peroxidase can objectively reflect the genetics among species. The use of peroxidase to assist in species identification is relatively simple and effective. In this work, we proposed a graphene-modified electrode. This electrode can amplify the signal of electrocatalytic reduction of hydrogen peroxide. Since peroxidase can catalyze the reduction of hydrogen peroxide, this signal can be used as an indicator to demonstrate the content of peroxidase in different plant tissues. Twelve herbal medicines were selected for our study. The results show that this electrochemical-based detection technique was comparable to colorimetric method in terms of accuracy.